Vindoline ameliorates intestinal barrier damage in Crohn's disease mice through MAPK signaling pathway. Issue 11 (5th October 2022) - Zhang, Xiaofeng; Zuo, Lugen; Geng, Zhijun; Song, Xue; Li, Jing; Ge, Sitang; Jiang, Yifan; Yang, Zi; Liu, Guangyong; Zhao, Yajing; Zhao, Hao; Yu, Liang; et al.
Abstract: Intestinal inflammation and intestinal barrier damage are important pathological changes in Crohn's disease (CD). Vindoline is a natural monomer with anti‐inflammatory effects. We employed CD model mice to explore the effect of Vindoline on CD‐like colitis and the possible mechanism . Il‐10 ‐deficient ( Il‐10 −/− ) mice and wild‐type (WT) mice (both aged 15 weeks, male) were used to explore the effect of Vindoline on colitis and intestinal barrier damage, as well as macrophage‐mediated inflammation. Bone‐marrow‐derived macrophages (BMDMs) and colonic organoids from mice were used to explore the inhibitory effect of Vindoline on macrophage‐mediated inflammation and the protective effect on inflammation‐induced intestinal barrier damage as well as the possible mechanism. We found that Vindoline significantly ameliorated colitis in CD mice, as evidenced by increased weight change and colon length and decreased the colon macroscopic injury score, histological inflammatory score, and the expression of pro‐inflammatory mediators. Vindoline also protected against intestinal barrier damage in CD mice. Furthermore, Vindoline inhibited macrophage‐mediated inflammation and protected against inflammation‐induced intestinal barrier damage in the coculture system. In addition, Vindoline ameliorated colitis in CD mice by protecting against inflammation‐induced intestinal barrier damage, which may be caused by inhibition of MAPK signaling pathway. This protective effect suggests that Vindoline has potential value for clinical application in the treatment of CD.